Novel stably transfected gene reporter human hepatoma cell line for assessment of aryl hydrocarbon receptor transcriptional activity: construction and characterization - Novotna, Aneta; Pavek, Petr; Dvorak, Zdenek (Environmental science & technology, 2011)
We constructed stably transfected gene reporter cell line AZ-AHR, allowing measurement of aryl hydrocarbon receptor (AhR) transcriptional activity. Human hepatoma HepG2 cells were transfected with a construct containing several AhR binding sites upstream of luciferase reporter gene. We prepared 12 clones and we characterized the best five in responsiveness to TCDD. Dose-response analyses were performed for various AhR ligands, including TCDD, 3-methylcholanthrene, indirubin, resveratrol, omeprazole, and SP600125. The EC(50) values were similar in all tested clones. Induction of luciferase was time-dependent, and treatment for 6 h with 5 nM TCDD was sufficient to evaluate AhR transcriptional activity in 96-well plate format (8-24 fold induction). Response to AhR ligands of cryopreserved cells after thawing was not significantly different from that of fresh cells. Cell line remained fully responsive to AhR ligands over 15 passages and 30 days in culture without significant alterations. Overall, we have developed novel human luciferase reporter cell line AZ-AHR for monitoring AhR transcriptional activity. The sensitivity of the assay allows high throughput format (96-well plate) and evaluation of luciferase activity as soon as after 6 h of incubation, which has potential implication for studies of cytotoxic compounds.
Keywords: omeprazol; polychlorované dibenzodioxiny; lidé; resveratrol; signální transdukce; Gene Expression; Luciferases; Anthracenes; Stilbenes; luciferasy; Omeprazole; Signal Transduction; Methylcholanthrene; Humans; Receptors, Aryl Hydrocarbon; exprese genu; buňky Hep G2; receptory aromatických uhlovodíků; Resveratrol; Indoles; stilbeny; Polychlorinated Dibenzodioxins; methylcholanthren; anthraceny; indoly; Transfection; transfekce; Hep G2 Cells